2020
DOI: 10.2196/preprints.24387
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barriers to and Facilitators of User Engagement With Digital Mental Health Interventions: Systematic Review (Preprint)

Abstract: BACKGROUND Digital mental health interventions, that deliver mental health support via technologies such as a mobile apps, can increase access to mental health support, and many studies have demonstrated their effectiveness in improving symptoms. However, user engagement, referring to a user’s uptake and sustained interactions with these interventions, varies. OBJECTIVE The aim of this systemat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 222 publications
0
6
0
Order By: Relevance
“…Baumel et al propose that because digital mental health interventions (DMHIs) require users to manage their health away from traditional care settings such as face-to-face therapy, the experiences must compete with other stimuli in everyday life, including other digital media. Furthermore, many other contextual factors -such as the nature and severity of a user's mental health symptoms and the extent the intervention is tailored to individual characteristics and preferences -can influence user engagement patterns with DMHIs [10].…”
Section: A Engagement With Digital Mental Health Interventionsmentioning
confidence: 99%
“…Baumel et al propose that because digital mental health interventions (DMHIs) require users to manage their health away from traditional care settings such as face-to-face therapy, the experiences must compete with other stimuli in everyday life, including other digital media. Furthermore, many other contextual factors -such as the nature and severity of a user's mental health symptoms and the extent the intervention is tailored to individual characteristics and preferences -can influence user engagement patterns with DMHIs [10].…”
Section: A Engagement With Digital Mental Health Interventionsmentioning
confidence: 99%
“…The accumulation of experiences of online media use has drawn researchers' attention and an interest in examining engagement within the online media environment. Involvement in the online context is described as user experience with the technology or a media brand (Borghouts et al, 2021;Mersey, Malthouse, & Calder, 2010). More concretely, online engagement is "a phenomenon where viewers or readers are completely invested in the unfolding of the media content, often oblivious to the surrounding environment" (Oh, Bellur, & Sundar, 2015, p.3).…”
Section: Affective Vs Cognitive News Engagementmentioning
confidence: 99%
“…In more recent years, digital interventions (DI) have become increasingly popular to overcome existing barriers in accessing mental health support (Borghouts et al, 2021). Studies have shown that DI have been effective in addressing barriers related to stigma and accessibility present within face-to-face interventions (Gulliver et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that DI have been effective in addressing barriers related to stigma and accessibility present within face-to-face interventions (Gulliver et al, 2010). Although DI in the form of mobile applications (apps) or websites have also been shown to present their own problems in that they are dependent on the ability to use and access digital technology (Dixon et al, 2016), they have shown to be highly effective in the treatment of mental health conditions (Borghouts et al, 2021).…”
Section: Introductionmentioning
confidence: 99%